Targeted inhibition of Rev‐erb‐α/β limits ferroptosis to ameliorate folic acid‐induced acute kidney injury. (23rd November 2020) - Guo, Lianxia; Zhang, Tianpeng; Wang, Fei; Chen, Xun; Xu, Haiman; Zhou, Cui; Chen, Min; Yu, Fangjun; Wang, Shuai; Yang, Deguang; Wu, Baojian
Abstract : Background and Purpose: Acute kidney injury (AKI) is a common and critical illness, resulting in severe morbidity and a high mortality. There is a considerable interest in identifying novel molecular targets for management of AKI. We investigated the potential role of the circadian clock components Rev‐erb‐α/β in regulation of ferroptosis and AKI. Experimental Approach: AKI model was established by treating mice with folic acid. Regulatory effects of Rev‐erb‐α/β on AKI and ferroptosis were determined using single‐gene knockout ( Rev‐erb‐α −/− and Rev‐erb‐β −/− ) mice, incomplete double‐knockout (icDKO, Rev‐erb‐α +/− Rev‐erb‐β −/− ) mice and cells with erastin‐induced ferroptosis. Targeted antagonism of Rev‐erb‐α/β to alleviate AKI and ferroptosis was assessed using the small‐molecule antagonist SR8278. Transcriptional gene regulation was investigated using luciferase reporter, mobility shift and chromatin immunoprecipitation assays. Key Results: Loss of Rev‐erb‐α or Rev‐erb‐β reduced the sensitivity of mice to folic acid‐induced AKI and eliminated the circadian time dependency in disease severity. This coincided with less extensive ferroptosis, a main cause of folic acid‐induced AKI. Moreover, icDKO mice were more resistant to folic acid‐induced AKI and ferroptosis as compared with single‐gene knockout mice. Supporting this, targeting Rev‐erb‐α/β by SR8278 attenuated ferroptosis to ameliorate folic acid‐induced AKI in mice. Rev‐erb‐α/β promoted ferroptosis by repressing the transcription of Slc7a11 and HO1 (two ferroptosis‐inhibitory genes) via direct binding to a RORE cis ‐element. Conclusion and Implications: Targeted inhibition of Rev‐erb‐α/β limits ferroptosis to ameliorate folic acid‐induced AKI in mice. The findings may have implications for improved understanding of circadian clock‐controlled ferroptosis and for formulating new strategies to treat AKI.